To pool or not to pool? Security design in OTC markets - Glode, Vincent; Opp, Christian C.; Sverchkov, Ruslan (Journal of Financial Economics, 2022)
We study security issuers’ decisions on whether to pool assets when facing counterparties endowed with market power, as is common in over-the-counter markets. Our analysis reveals how buyers’ market power may render the pooling of assets suboptimal — both privately and socially — in particular, when the potential gains from trade are large. Pooling assets then reduces the elasticity of trade volume in the relevant part of the payoff distribution, exacerbating the inefficient rationing associated with the exercise of buyers’ market power. Our analysis provides insight on the determinants of asset-backed securities issuance, including regulatory reforms affecting financial institutions’ liquidity.